Ethical gap to implement utilitarianism in healthcare policy: A hidden Pandemic Ethics Crisis. - Ranju, Gausul Azam; Serice, Tania (Bangladesh Journal of Medical Science, 2021)
Abstract not available Bangladesh Journal of Medical Science Vol.20(5) 2021 p.178-182